Rekonstruksi Landasan Biblika bagi Evaluasi Pendidikan Agama Kristen di Era Digital - Simon; Jerie Refni Boy Maarende (Institut Kristen Teologi Real Batam, 2026)
This article is written based on the researcher’s observation that studies related to the evaluation of Christian Religious Education still tend to focus on aspects related to the curriculum, teaching methods, and educators. However, the aspect of PAK evaluation based on Biblical foundations is still very rarely researched, which prompted the author to examine this topic. The formulation of the main research question posed from this topic is: what is the concrete reconstruction of the biblical foundation for the evaluation of Christian Religious Education (CRE) in the digital era? In outlining this paper, the author uses a literature study approach as the main strategy to reconstruct the biblical foundation in the evaluation of Christian Religious Education (CRE) in the digital era. This methodological approach was chosen not for the collection of numerical data but for the understanding of conceptual meaning. The findings of this study present the concept of evaluation in the Bible as never merely understood as an intellectual measurement, but rather as an assessment of the authenticity of faith manifested in concrete life. Therefore, the conceptual evaluation (PAK) based on biblical reconstruction needs to be designed as an integrative framework that combines normative-theological dimensions and contextual pedagogical dimensions. Keywords: biblical foundation; Christian religious education; digital era; learning evaluation; theological reconstruction Abstrak Artikel ini ditulis atas pengamatan peneliti bahwa penelitian yang berkaitan dengan evaluasi Pendidikan Agama Kristen masih cenderung bertumpu pada tataran terkait kurikulum, metode mengajar, dan juga pendidik. Akan tetapi, aspek evaluasi PAK dalam landasan Biblika masih sangat jarang diteliti, hal ini mendorong penulis mengkaji topik ini. Rumusan pertanyaan penelitian utama yang diajukan dari topik ini seperti apa kongkrit dari rekonstruksi landasan biblika bagi evaluasi PAK di era digital? Di dalam menguraikan tulisan ini, penulis menggunakan pendekatan studi literatur sebagai strategi utama untuk merekonstruksi landasan Biblika dalam evaluasi Pendidikan Agama Kristen (PAK) di era digital. Pendekatan metodologis itu dipilih bukan pada pengumpulan data numerik melainkan pemahaman makna konseptual. Temuan kajian ini mengemukakan konsep evaluasi dalam Alkitab tidak pernah dipahami sekadar sebagai pengukuran intelektual, melainkan sebagai penilaian terhadap autentisitas iman yang termanifestasi dalam kehidupan konkret. Oleh sebab itu, konseptual evaluasi (PAK) berbasis rekonstruksi biblika perlu dirancang sebagai suatu kerangka integratif yang memadukan dimensi normatif-teologis dan dimensi pedagogis kontekstual. Kata Kunci: era digital; evaluasi pembelajaran; landasan biblika; pendidikan agama Kristen; rekonstruksi teologis